2007
DOI: 10.1258/095646207779949880
|View full text |Cite
|
Sign up to set email alerts
|

High hepatitis C virus prevalence and incidence among Canadian intravenous drug users

Abstract: We used data and leftover samples collected through the SurvUDI network to describe the epidemiology of hepatitis C virus (HCV) infection among injection drug users (IDUs) in Eastern Central Canada. Among the 1380 selected IDUs, having participated twice or more between 1997 and 2003, the overall HCV prevalence rate was 60.4% (95% confidence interval [CI]: 57.7-63.0%). Among the 543 initially uninfected participants, the HCV incidence rate was 27.1 per 100 person-years (95% CI: 23.4-30.9 per 100 person-years).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 11 publications
5
86
0
1
Order By: Relevance
“…In total, we included 21 published studies 14,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and seven unpublished studies [33][34][35][36][37]59,60 comprising 1827 HCV incident infections and 8789.7 person-years of follow-up. Overall HCV infection incidence ranged between 0.09 and 42 cases per 100 person-years across the studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, we included 21 published studies 14,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and seven unpublished studies [33][34][35][36][37]59,60 comprising 1827 HCV incident infections and 8789.7 person-years of follow-up. Overall HCV infection incidence ranged between 0.09 and 42 cases per 100 person-years across the studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…[33][34][35][36][37]59,60 Seventeen studies reported the impact of NSPs, 14,20,[41][42][43][44]47,48,50,54,56,58 including five unpublished sources, [33][34][35]59,60 and four reported combined measures of NSPs with OST, 14,33,44,47 including one unpublished data source. 33 One study looked at the impact of distributing injecting paraphernalia (defined as spoons and filters) by itself, with needles/syringes and in combination with OST.…”
Section: Type Of Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The behavioural and psychosocial components of the questionnaire were developed by adapting elements from the SurvUDI study questionnaire of IDUs in Quebec (Roy et al, 2007), the Montreal Street Youth Cohort (Roy et al, 1998), the Bloodborne Virus Transmission Risk Assessment Questionnaire used in Australia (Fry & Lintzeris, 2003), and the Diffusion of Benefits Through Syringe Exchange Program Project Questionnaire used in the United States (Grau, Bluthenthal, Marshall, Singer, & Heimer, 2005). Items pertaining to the model variables were developed through an iterative process involving several steps.…”
Section: Data Collectionmentioning
confidence: 99%